Use of Advanced Foreign Experiences in Increasing the Efficiency of Classroom and Out-of-Class Lessons. - Saidova Gavhar Ergashovna; Avliyokulova Nasiba Choriyevna (Zien Journals, 2023)
This article describes methods and methods of using advanced foreign experiences and learning advanced pedagogical experience to improve the effectiveness of classroom and extracurricular reading lessons of elementary school students.
Keywords: advanced pedagogical experience; modern technology; innovative pedagogical technology; educational goal